CLOUD COMPUTING: BEGINNING OF A NEW TECHNICAL ERA (International Journal of Engineering and Computer Science, 2014)
With the arrival of new era of technology , incremental use of gadgets such as smart phones loaded with camera , tablets ,music players, hand held game consoles etc. has led to a continuous requirement to store , share and access digital data .Thus massive digital data born every day requires a huge storage which can only be fulfilled by cloud.. [13]. Cloud computing allows the storage and processing of data over huge data centres and facilitates an on demand delivery of services over a computer network (typically Internet) . With the development of IC technology and advancement of VLSI andULSI technologies, consumers are made available modern day computes with high processing capability which could not be utilized to its fullest .In this paper we have explained how this problem  is solved with use of  Virtualization technique.This paper is a brief survey based on reading of cloud computing and it tries to explains how services are delivered in cloud computing ,  gives the basic concepts, general architecture of cloud, and fundamental software for virtualization called hypervisor.[2]